2020
DOI: 10.4103/2045-9912.304221
|View full text |Cite
|
Sign up to set email alerts
|

Two weeks of hydrogen inhalation can significantly reverse adaptive and innate immune system senescence patients with advanced non-small cell lung cancer: a self-controlled study

Abstract: Following standard treatments, the traditional model for enhancing anti-tumor immunity involves performing immune reconstitution (e.g., adoptive immune cell therapies or immunoenhancing drugs) to prevent recurrence. For patients with advanced non-small cell lung cancer, we report here on two objectives, the immunosenescence for advanced non-small cell lung cancer and hydrogen gas inhalation for immune reconstitution. From July 1 st to September 25 th , 2019, 20 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For advanced NSCLC patients, the immune senescence involved nearly all lymphocyte subsets, and 2 weeks of hydrogen treatment significantly improved most of these indexes. 20 The effects of hydrogen therapy on advanced NSCLC patients and middle-aged non-tumor participants in this study appear to be contradictory. The reason for this may be that the lymphocytes of patients with progressive tumors and those of non-tumor patients are quite different.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…For advanced NSCLC patients, the immune senescence involved nearly all lymphocyte subsets, and 2 weeks of hydrogen treatment significantly improved most of these indexes. 20 The effects of hydrogen therapy on advanced NSCLC patients and middle-aged non-tumor participants in this study appear to be contradictory. The reason for this may be that the lymphocytes of patients with progressive tumors and those of non-tumor patients are quite different.…”
Section: Discussionmentioning
confidence: 64%
“… 16 Thus, we tested whether hydrogen gas inhalation can rescue the function of exhausted and senescent lymphocytes, as hydrogen gas was reported to protect the mitochondrial function of human lymphocytes. 17 18 19 By comparing the immune functions of advanced non-small cell lung cancer patients before and after hydrogen inhalation, we found that 2 weeks of hydrogen inhalation was enough to reverse multiple senescent or exhausted cell subsets into functional subsets, 20 so we used the same hydrogen inhalation duration during this study. There were no obvious changes in any T cell subsets due to hydrogen inhalation in either cell number, memory phenotype, differentiation phenotype or senescent or exhausted phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, reports indicated that the antioxidant effect of H 2 was dose-dependent, and the concentration of H 2 in blood and tissues was dependent on the time and concentration of inhalation (Fukuda et al, 2007 ). In recent years, the administration of a mixture of H 2 and O 2 gases (66% H 2 ; 33% O 2 ), obtained by the electrolysis of water, for research and clinical investigation has become more and more common (Li H. et al, 2017 ; Chen et al, 2020 ). The application of high concentrations of H 2 gas may result in more effective outcomes.…”
Section: Molecular Hydrogenmentioning
confidence: 99%